Antihyperglycemic and antihyperlipidemic properties of aqueous root extract of Icacina senegalensis in alloxan induced diabetic rats - GC Akuodor; PM Udia; A Bassey; KC Chilaka; OA Okezie (Journal of Acute Disease, 2014)
Objective: To evaluate the antidiabetic and hypolipidemic activity of aqueous root extract of Icacina senegalensis (I. senegalensis) in alloxan-induced diabetic rats. Method: Blood glucose levels of alloxan-induced diabetic rats were monitored after the administration of I. senegalensis extract (100, 200 and 400 mg/kg) to diabetic rats for 14 d. Different biochemical parameters, serum cholesterol, serum triglyceride, high density lipoprotein, low density lipoprotein and very low density lipoprotein were also examined. Results: Treatment of alloxan diabetic rats with the extract showed significant (P<0.05) activity. The activity of the extract was comparable to that of the standard drug, glinbeclamide. Conclusions: The results suggest that the root extract of I. senegalensis possesses antidiabetic and hypolipidemic properties, which might be a potential source for isolation of new orally active agent in the treatment of diabetes and its associated complications.